What Is It Like to Sound Like a Bot? - Paxton, Amanda (Discourse and Writing/Rédactologie, 2023)
This article proposes that the rise of GPT technology presents an opportunity to initiate meaningful discussions in the postsecondary classroom about the connections between writing, language, and personal autonomy. Partly grounded on predictive text, GPT-produced language is often recognizable by its blandness and its proneness to the predictable turn of phrase—qualities that postsecondary students (among others!) often struggle to overcome in their own work. George Orwell famously described relying on cliché as akin to turning oneself into a machine. The analogy arises from the lack of relationality in cliché-riddled writing, a quality similarly found in AI-generated text. Rhetoric and composition theory provides insights into the relational nature of written discourse and, equally, into the places where GPT technology falls short of the profoundly intersubjective and interpersonal elements underlying written communication. Foregrounding these findings in class discussions of GPT tools is a central task in training students to engage critically with such tools. Assignments inviting students to contextualize themselves as writers—linguistically, culturally, discursively—represent an actionable step to help students identify the relational and interpersonal contexts to which GPT output cannot attend.